Multicenter Evaluation of Morbidity and Predictors of Response to Imiquimod Treatment for Penile Intraepithelial Neoplasia - Ofir Avitan; Laura Elst; Manon Vreeburg; Tynisha Rafael; Katja Jordanova; Niels Graafland; Kees Hendricksen; Bas W.G. van Rhijn; Henk G. van der Poel; Maarten Albersen; Oscar Brouwer (European Urology Open Science)
Introduction and objective: Imiquimod (IQ) is an immunomodulator used in the management of penile intraepithelial neoplasia (PeIN) lesions. However, IQ treatment may be associated with bothersome side effects (SEs). To date, studies reporting on this morbidity and evaluating predictors of response to IQ are scarce and included small cohorts. The primary objective of our study was to assess the response to IQ treatment, associated SEs, and potential predictors of response in the largest reported cohort to date. Methods: We conducted a collaborative retrospective study involving patients diagnosed with PeIN and treated with IQ between 2010 and 2022 in two high-volume centers in the Netherlands and Belgium. Eligible patients had a confirmed diagnosis of PeIN and a minimum of 6-mo follow-up. Response to IQ was categorized as a complete response (CR), partial response, or no response. Descriptive statistics were generated and statistical tests included the Mann-Whitney U test for age and Fisher’s exact test for categorical variables. Key findings and limitations: The study included a total of 44 patients, with a median age of 65.4 yr (interquartile range 56–72). Of these patients, 28 (64%) achieved a CR, while 14 (32%) had a partial response and two (4.5%) had no response. In the CR subgroup, the 3-yr recurrence rate was 25%. No significant correlation was found between response status and age, human papillomavirus status, history of penile cancer, or circumcision before treatment. Among the patients, 50% reported SEs, mainly local pain, irritation, and bleeding, and 12% discontinued treatment because of SEs. There was no significant correlation between CR and the incidence or type of SE. Conclusions and clinical implications: Despite the high overall response rate to IQ, a significant number of patients experienced local recurrence within 3 yr, and approximately half of the patients reported SEs. Our results did not identify any clinical or pathological factors or local SEs predictive of the therapeutic response to IQ. Prospective studies are needed to help in predicting which patients are likely to respond to IQ so that those who will not benefit can be spared the SEs associated with this treatment. Patient summary: Our study looked at responses to imiquimod (IQ), an immune-based treatment in cream format, for precancerous lesions on the penis, called penile intraepithelial neoplasia. More than 95% of patients had a complete or partial response to IQ, but 50% reported side effects, and 25% of the group with a complete response had recurrence within 3 years. More research is needed to help in selecting patients who will benefit the most from IQ treatment.